Wire electrical discharge machining for microfabrication - Ali, Mohammad Yeakub; N.I, Rashidah; N.A, Azima (2007)
This paper discusses the application of conventional wire electrical discharge machining (WEDM) for fabrication of miniaturized components using low pulse energy. The surface finish of the fabricated microparts was investigated for different level of discharge current at constant gap voltage and pulse-on time. Miniaturized gears of 3.58 mm outside diameter were fabricated from copper blank as an example. The fabricated microgears were inspected by using scanning electron microscope (SEM) (JSM-5600, JEOL, Japan) where higher accuracy and geometrical integrity were observed. The surface roughness of the microgear was measured by using surface profiler (Surftest SV-500, Mitutoyo, Japan). An average surface roughness (Ra) of 1.8 μm and dimensional accuracy of 1-2% were achieved.